Respostas cardiovasculares ao teste de preensão manual em policiais militares com e sem apneia obstrutiva do sono - Nascimento, Reginaldo Ceolin Do (2021)
The aim of the present study was to evaluate the influence of obstructive sleep apnea (OSA) on the integrity of cardiovascular responses to the handgrip test (HT) in military police officers (MP). For this purpose, MP from the state of São Paulo, Brazil (35-55 years) were evaluated, at rest and three minutes of HT, as the cardiovascular responses of blood pressure (BP), heart rate (HR) and HR variability (HRV). The groups without OSA (<5 events/hour, n=9) and with OSA (≥15 events/hour, n=10) were compared and the relationship of cardiovascular responses with sleep indicators was tested. It was possible to observe that the group with OSA presented SBP (134 ± 15 vs. 116 ± 9, p=0.006) and DBP (81 ± 11 vs. 66 ± 5, p=0.002) higher values at rest than the group without OSA. However, cardiovascular responses during PMS were similar for SBP (p=0.438), DBP (p=0.487), HR (p=0.190) and HRV indicators (p>0.540). At rest, SBP and DBP correlated positively with sleep quality indicators (hypopnea apnea index and obstructive apnea index, rho>0.494, p<0.014) and negatively correlated with minimum oxygen saturation (rho>-0.650, p <0.006). During HT, there was a relation between total snoring and the highest value obtained for HR (rho=0.659, p=0.006), as well as HR and HRV indicators with mean HR during sleep (rho>0.518, p<0.040). In conclusion, although the OSA group had worse cardiovascular indicators at rest, the cardiovascular responses to TPM of PMs with and without OSA are similar.